STUDY ON TECHNIQUES AND TOOLS USED IN LEAN HEALTHCARE IMPLEMENTATION: A LITERATURE REVIEW - Senna, Pedro; Gomes, Andreia; Monteiro, Aluisio; Pinha, Denis (Brazilian Journal of Operations & Production Management, 2016)
Lately, Lean philosophy is increasingly gaining importance due to a competitive environment, which creates the need of reducing costs. Lean practices and tools have been applied to manufacturing, services, supply chains, startups and the next frontier is Healthcare. Most of lean techniques can be easily brought to Healthcare organizations. Therefore, this paper aims to summarize Lean practices and tools which are already being applied to Healthcare organizations. As its main results, we can highlight main authors, papers and number of publications per year and so, this paper can be used as a guideline for Lean implementations in Healthcare organizations.